Perancangan Dan Pembuatan Komponen Undercarriage Pada Model Excavator Di Laboratorium Hidraulik Dan Pneumatik Universits Riau - Kiki Gunawan; Nazaruddin Nazaruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Excavator is units of the heavy equipment that serves the physical development sectors such as mining excavations in the area , establishing or expanding roads and expand agricultural land and other physical development . One part of the excavator that has a very large role in the undercarriage . Undercarriage is a component of the heavy equipment that serves as a driver and has a track drive right and left track drive . This research was conducted with the aim to make modeling as excavators in general by using materials available in the market . Next calculate the speed , direction of turn with a different variation of the track ( ceramic , asphalt , soil ) and the maximum tilt angle that can be achieved by the excavator . From the test data and calculations have been carried out with 3 times the gear reduction is obtained without load speed excavator bucket is 0.25 m / s while using a load of 1.5 kg bucket excavator speed is 0.24 m / s at the track ceramics . While the direction of maximum inflection occurs on the track with a diameter ceramic to turn right for 995 mm and 782 mm turn left . At the maximum angle of incline can be obtained at 10 degrees .  Key Word : excavator, undercarriage